2005
DOI: 10.1103/physrevc.71.029902
|View full text |Cite
|
Sign up to set email alerts
|

Publisher's Note: Measurements of cross sections and decay properties of the isotopes of elements 112, 114, and 116 produced in the fusion reactionsU233,238,Pu

Abstract: Publisher's Note: Measurements of cross sections and decay properties of the isotopes of elements 112, 114, and 116 produced in the fusion reactions 233,238 U, 242 Pu, and 248 Cm+ 48 Ca [Phys. Rev. C 70, 064609 (2004)]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 0 publications
4
36
0
Order By: Relevance
“…Prior work has shown that the competition between fusionfission and quasifission is affected by shell driven deformation and orientation [4][5][6][7][8]. In this work we show that the quasifission process is strongly influenced by shell effects encountered during the evolution of the dinuclear system.…”
Section: Introductionsupporting
confidence: 48%
“…Prior work has shown that the competition between fusionfission and quasifission is affected by shell driven deformation and orientation [4][5][6][7][8]. In this work we show that the quasifission process is strongly influenced by shell effects encountered during the evolution of the dinuclear system.…”
Section: Introductionsupporting
confidence: 48%
“…(See [1] for a review and [2][3][4][5][6][7][8] and references therein for details). These studies have used neutron-rich 48 Ca projectiles reacting with targets of actinide nuclei.…”
Section: Recent Searches For New Elementsmentioning
confidence: 99%
“…Over the years, some of these nuclei (up to Z = 111, Rg) have been discovered in Berkeley, Dubna and Darmstadt [38][39][40]. There are many solid indications that the relative stability of these nuclei is caused by a strong prolate shell effect.…”
Section: From Actinides To Superheaviesmentioning
confidence: 99%